2008
DOI: 10.1080/01676830701376072
|View full text |Cite
|
Sign up to set email alerts
|

Results of Levator Excision Followed by Fascia Lata Brow Suspension in Patients with Congenital and Jaw-Winking Ptosis

Abstract: Excision of the levator muscle followed by brow suspension ptosis correction can reliably produce satisfactory cosmetic results with good symmetry of lid movement and position. It is used selectively in the normal upper lid in congenital ptosis with poor levator function and in both upper lids in synkinetic ptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Mean age of our patients was 11.12 years. Other studies also reported the similar age group of presentation; mean age of 5 years, 5 11.23 yeas. 6 In our study, 78% of patients were males although other studies did not have such a difference in frequency among male and females.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Mean age of our patients was 11.12 years. Other studies also reported the similar age group of presentation; mean age of 5 years, 5 11.23 yeas. 6 In our study, 78% of patients were males although other studies did not have such a difference in frequency among male and females.…”
Section: Discussionmentioning
confidence: 49%
“…6 In our study, 78% of patients were males although other studies did not have such a difference in frequency among male and females. 5,7,8 Along with jaw winking, these patients also have various degree of ipsilateral ptosis and hypotropia. Many children learn to hold the jaw in a particular position to minimize the ptosis which Bower and Sullian describe it as patients 'habitual ptosis', which is often less than the patients true ptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In complex congenital ptosis, where patients have associated Marcus Gunn jaw winking phenomenon, ablation of a portion of the LPS muscle via an eyelid crease incision and resuspension of the eyelid to the brow are necessary, to abolish the associated synkinetic wink. 20 This incision also leads to the development of a well-defined eyelid crease, leading to superior patient satisfaction. The difference clearly lies in the presence of the eyelid crease and the upper eyelid tarsal show, post silicone sling frontalis suspension ptosis surgery, in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of ptosis patients with poor LPS action have a congenitally weak LPS muscle, which is thin, dystrophic and atonic. 20 After conventional frontalis sling suspension surgery, this nonfunctional muscle bunches up and forms a fullness in the preseptal upper lid area. The absence of the tarsal show leads to further dissatisfaction in female patients, who complain that they have no place to apply eye mascara and/or eye shadow, in the eye that has been operated on, post ptosis surgery.…”
Section: Discussionmentioning
confidence: 99%